Assessing the Impact of a Structured Educational Initiative on Awareness of Vaginitis and Its Prevention Among Adolescent Girls in Selected Higher Secondary Schools in Bengaluru - Aruna Mary C.; Rashmi Ramji M.R.; Swarnali Dey; S. Aneesha; Elsvin Greeshma George; Priyanka Aji Mathew; Smritikana Maji; Sindhu K.N.; Pallabi Prasa; Anjali S.; Rajkiran Ignatius; Joel Philip (International Journal of Midwifery Nursing And Practices, 2024)
Background and Objectives: Vaginal inflammation, referred to as vaginitis, may culminate in discharge, itching, and pain. Usually, the root cause is an infection or an altered in the balance of the microbes in the vagina. In females between the ages of two and six, poor perineal hygiene—such as wiping after bowel movements from back to front or not washing hands afterward—is an important contributory factor. Another typical sign is frequent stroking of the vagina or perineum, particularly in response to itching. Little objects are occasionally pushed by children into bodily cavities, such as the vagina. Tissue paper is one example of a foreign object that can cause non-specific vaginitis, which discharges blood. Vaginal infections are managed with antibiotics, and changing pads and tampons frequently is a prophylactic step. Objectives (1) To evaluate the pre-test knowledge level about vaginitis and its prevention among adolescent girls at selected higher secondary schools in Bengaluru. (2) To assess the effectiveness of a structured teaching program on knowledge related to vaginitis and its prevention among adolescent girls. (3) To examine the association between pre-test knowledge scores and their chosen socio-demographic variables. Methods: The research strategy utilized for this study was a pre-experimental one-group pre-test and post-test design. A total of 60 teenage girls were randomly selected using the random sampling technique. The structured knowledge questionnaire Tool was employed to measure their knowledge levels. Following the initial assessment, the adolescent girls participated in the structured teaching program. A post-test was conducted on the eighth day using the same instrument. Utilizing both descriptive and inferential statistics, the outcomes were explained. Results: During the process of gathering data, 71.7% of participants knew nothing about vaginitis in teenage females, 28.3% knew something about it, and 0% knew enough. In the post-test, 48.3% of respondents had moderate knowledge, 51.7% had appropriate knowledge, and 0.0% had insufficient knowledge. Interpretation and Conclusion: The results of the study demonstrate the effectiveness of a systematic training program in raising teenage girls’ awareness of vaginitis.
Keywords: Adolescent girls; Knowledge; effectiveness; structured teaching program; vaginitis